Momordica charantia L. with Oxy Combination of Momordica charantia L. with oxytetracycline enhanced antibacterial and antibiofilm activities against some multidrug-resistant bacteria - Kongcharoensuntorn, Wisatre; Inthasorn, Araya; Kraekrathok, Chadaphorn; Chiangthong, Sirimas; Dujjanakee, Wachiraya (Journal of Associated Medical Sciences, 2024)
Background: Momordica charantia L., the common name for bitter gourd, frequently used as a vegetable and in traditional medicine to treat wounds, peptic ulcers, parasites, and worms. Regarding of finding alternative ways to cure nosocomial infection caused by multidrug-resistant bacteria, bitter gourd in combination with some antibiotics may be a practical choice to reduce the cost of therapy and be devoid of side effects from antibiotics. Objective: This study aimed to determine the antimicrobial, antibiofilm, and synergy effects of ethanol extract from bitter gourd in combination with conventional antibiotics, ampicillin, and oxytetracycline against some drug-resistant bacteria. Materials and methods: The antimicrobial activity was tested by broth microdilution, and the lowest concentration that inhibits the visible growth of each microorganism was recorded as MIC. A checkerboard microdilution assay was designed to test the synergistic effect of bitter gourd extract. A crystal violet staining assay was carried out to test antibiofilm activity Results: The bitter gourd extracted by ethanol revealed antibacterial activity with a MIC range of 1.25-80 mg/mL. Synergistic effects of bitter gourd extract with ampicillin and oxytetracycline were effective against P. mirabilis and drug-resistant P. aeruginosa growth by FICI at 0.141 and 0.63, respectively. The results found that bitter gourd exhibited antibiofilm activities against E. coli ATCC 25922, drugresistant P. aeruginosa, and Methicillin-Resistant Staphylococcus aureus (MRSA) at 2-4 hours after starting inoculum and the inhibitory efficacy values were 37.62%, 71.14%, and 69.87%, respectively. Conclusion: The ethanol extract from bitter gourd had antibacterial effect, synergy effect when mixed with ampicillin and oxytetracycline.